Contexts, Impulses and Themes of National Contemporary Choreographic Creation. What Trends? - Xavier, Madalena (2016)
In this reflection we seek to systematize issues relating to the processes of contemporary choreography and themes that can reveal aspects of its conceptual, motivational and contextual dimension. Given the complexity and scope of the theme three national reference choreographers were focused – Clara Andermatt, Paulo Ribeiro and Victor Hugo Pontes – in their dance creations between 2011 and 2014.This reflection relies on documents analysis, interviews and artistic synopses issued by the support structures and theaters.We conclude that the creative context is very wide and diversified; that the impulse for creation can have different dimensions, one centered on the will and needs of the choreographer himself/herself, but also from exterior challenges; and distinct dimensions were identified, relating to the theme definition of the dance piece